Development of a Deep Learning–Based Picture Storybook for Grade II Elementary School Students - Retna Ayu Rachmawati; Sudirman Sudirman; Sukri Sukri (International Journal of Social Sciences and Humanities, 2026)
The limited availability of picture storybooks that align with students’ characteristics, along with the lack of integration of deep learning principles in Grade II Indonesian language instruction, indicates the need to develop relevant and contextual learning media that meet students’ learning needs. This study aims to develop a deep learning–based picture storybook that is feasible for use in Grade II elementary school learning. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were Grade II teachers and students at MI Integral Buah Hati Insani Mataram. Data were collected through interviews, observations, expert validation questionnaires (material and media), and teacher and student response questionnaires. The results showed that the developed picture storybook obtained a validity score of 95% from material experts and 97% from media experts, both categorized as highly feasible. In the development class trial (n = 12), teacher responses reached 96% and student responses 85%. Meanwhile, in the extended trial (n = 14), teacher responses reached 96% and student responses 89%, both categorized as highly practical. Therefore, the developed deep learning–based picture storybook is considered feasible to be used as a supporting instructional material for Indonesian language learning in elementary schools.